Pengaruh Reward System dan Enterpreneurial Leadership untuk Meningkatkan Employee Performance Melalui Employee Satisfaction pada Perusahaan Building Material: Study Pada CV. Nusantara Putra Purnama - Romdhoni, Muhammad Farich; Harianto, Eric (Ikatan Da'i Indonesia, 2024)
This study examines the effect of reward system and entrepreneurial leadership on employee performance mediated by employee satisfaction in the context of a building materials company, CV. Nusantara Putra Purnama, in Jember. This study used a quantitative approach with a saturation technique to collect data from a sample of employees and the required sample of 40 people. Data were obtained through an online questionnaire using Google Form. The hypothesis test in this study shows that the reward system, entrepreneurial leadership, and employee satisfaction affect employee performance. The findings contribute to the theoretical understanding of organizational behavior and provide practical insights for improving employee performance through strategic leadership and reward management.